Tafsir Nusantara in the Science Field: A Bibliometric Analysis in 2011-2022 Using Scopus Database - Noor, Faiq Makhdum; Asriyadin, Asriyadin (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
Tafsir Nusantara in the Science Field: A Bibliometric Analysis in 2011-2022 Using Scopus Database. The study of tafsir nusantara is a cultural product that was born from the dialectical process between the mufassir and the cultural reality. This research aims to analyze the study of tafsir nusantara in the science field using bibliometric techniques from 2011-2022. This research was conducted on August 25, 2022. The data obtained were 16 documents taken from the Scopus database with the keyword "tafsir nusantara in the science field". The data was mapped using VOSviewer software. Based on the results of the study, it can be seen that research of tafsir nusantara in the science field is still limited. According to Scopus data, research on tafsir nusantara in the science field has only been around since 2011. The dominant language used is English with 14 documents, Arabic for 1 document, and Malay for 1 document. The most dominant countries that contributed articles were Indonesia with 6 documents, Malaysia with 5 documents, and other countries with only 1 document. Based on the Vosviewer visualization, all research resulted in four clusters. The first cluster is related to research, qualitative methodology, and data analysis. The second cluster is related to Indonesia, traditions, and religion. The third cluster relates to the influence of Islam, history, and the Qur'an. The fourth cluster deals with Malaysia, curriculum, and students. Thus, this research is targeted to find out the development of tafsir nusantara research in the science field and to assist future research.